2020
DOI: 10.1038/s41598-020-58062-y
|View full text |Cite
|
Sign up to set email alerts
|

An intra-bacterial activity for a T3SS effector

Abstract: Many Gram-negative bacterial pathogens interact with mammalian cells by using type iii secretion systems (T3SS) to inject virulence proteins into host cells. A subset of these injected protein 'effectors' are enzymes that inhibit the function of host proteins by catalyzing the addition of unusual posttranslational modifications. The E. coli and Citrobacter rodentium NleB effectors, as well as the Salmonella enterica SseK effectors are glycosyltransferases that modify host protein substrates with N-acetyl gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 46 publications
2
29
1
1
Order By: Relevance
“…In addition, NleB/SseK proteins may catalyze the glycosylation of endogenous bacterial proteins. A recent report has shown that NleB1 from enterohemorrhagic E. coli, NleB from C. rodentium, and SseK1 from S. enterica, can glycosylate the bacterial protein GshB (glutathione synthetase) [31]. This glycosylation enhances GshB-mediated production of glutathione, which provides resistance to oxidative stress, suggesting a new role for these effectors in promoting the survival of bacteria under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NleB/SseK proteins may catalyze the glycosylation of endogenous bacterial proteins. A recent report has shown that NleB1 from enterohemorrhagic E. coli, NleB from C. rodentium, and SseK1 from S. enterica, can glycosylate the bacterial protein GshB (glutathione synthetase) [31]. This glycosylation enhances GshB-mediated production of glutathione, which provides resistance to oxidative stress, suggesting a new role for these effectors in promoting the survival of bacteria under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent report has shown that NleB1 can also glycosylate a bacterial protein, GshB (glutathione synthetase) on Arg 256 . In fact, this was the most abundant arginine-GlcNAcylated target enriched from samples of HEK293T cells infected with EHEC [179]. GshB was also glycosylated in vitro and in vivo by C. rodentium NleB and in vitro by Salmonella SseK1.…”
Section: Targets Of Nleb/ssek Effectorsmentioning
confidence: 99%
“…Remarkably, in more recent work, Wuhan Xiao and co-workers discovered that HIF-1α was GlcNAcylated at a conserved arginine (Arg18) during C. rodentium or EPEC infection, and the modification enhanced HIF-1α transcriptional activity, thus inducing downstream glucose metabolism-associated gene [such as glucose transporter 1 (GLUT1) gene] expression to alter host glucose metabolism (Xu et al, 2018). Additionally, a more recently study has shown that bacterial glutathione synthetase (GshB) was GlcNAcylated by C. rodentium NleB on Arg256 (El Qaidi et al, 2020). Further, NleBmediated GlcNAcylation of GshB contributed to C. rodentium survival in oxidative stress conditions (El Qaidi et al, 2020).…”
Section: Arginine N-acetylglucosamine Transferase In Pathogenic E Comentioning
confidence: 99%